Synthesis, IR and 13C-NMR Spectral Studies of Some 2-Pyrazolin-5-One Derivatives - J. Kharodawala, Mohammad; K. Rana, Arjun (Asian Journal of Chemistry, 2010)
4-Formyloxime-3-methyl-1-(2´,4´-dinitrophenyl)-2-pyrazolin-5-one, 4-formyloxime-3-phenyl-1-(2´,4´-dinitrophenyl-pyrazolin-5-one, 4-formyl-oxime-1-3-diphenyl-2-pyrazolin-5-one, 4-acetyloxime-3-phenyl-1-(2´,4´-dinitrophenyl)-2-pyrazoline-5-one, 4-benzoyloxime-3-methyl-1-(2´,4´-di-nitrophenyl)-2-pyrazolin-5-one, 4-oximino-3-methyl-1-(2´,4´-dinitro-phenyl)-2-pyrazolin-5-one, 4-oximino-3-phenyl-1-(2´,4´-dinitrophenyl)-2-pyrazolin-5-one have been synthesized. The elemental analysis, m.p., yield (%) FT-IR and 13C-NMR spectral studies of all compounds have been reported.